Role of Lysine‐Specific Demethylase 1 in Metabolically Integrating Osteoclast Differentiation and Inflammatory Bone Resorption Through Hypoxia‐Inducible Factor 1α and E2F1 - Doi, Kohei; Murata, Koichi; Ito, Shuji; Suzuki, Akari; Terao, Chikashi; Ishie, Shinichiro; Umemoto, Akio; Murotani, Yoshiki; Nishitani, Kohei; Yoshitomi, Hiroyuki; Fujii, Takayuki; Watanabe, Ryu; et al. (Arthritis & rheumatology (Hoboken, N.J.), 2022)
Objective Hypoxia occurs in tumors, infections, and sites of inflammation, such as in the affected joints of patients with rheumatoid arthritis (RA). It alleviates inflammatory responses and increases bone resorption in inflammatory arthritis by enhancing osteoclastogenesis. The mechanism by which the hypoxia response is linked to osteoclastogenesis and inflammatory bone resorption is unclear. This study was undertaken to evaluate whether the protein lysine‐specific demethylase 1 (LSD1) metabolically integrates inflammatory osteoclastogenesis and bone resorption in a state of inflammatory arthritis. Methods LSD1‐specific inhibitors and gene silencing with small interfering RNAs were used to inhibit the expression of LSD1 in human osteoclast precursor cells derived from CD14‐positive monocytes, with subsequent assessment by RNA‐sequencing analysis. In experimental mouse models of arthritis, inflammatory osteolysis, or osteoporosis, features of accelerated bone loss and inflammatory osteolysis were analyzed. Furthermore, in blood samples from patients with RA, cis‐acting expression quantitative trait loci (cis‐eQTL) were analyzed for association with the expression of hypoxia‐inducible factor 1α (HIF‐1α), and associations between HIF‐1α allelic variants and extent of bone erosion were evaluated. Results In human osteoclast precursor cells, RANKL induced the expression of LSD1 in a mechanistic target of rapamycin–dependent manner. Expression of LSD1 was higher in synovium from RA patients than in synovium from osteoarthritis patients. Inhibition of LSD1 in human osteoclast precursors suppressed osteoclast differentiation. Results of transcriptome analysis identified several LSD1‐mediated hypoxia and cell‐cycle pathways as key genetic pathways involved in human osteoclastogenesis. Furthermore, HIF‐1α protein, which is rapidly degraded by the proteasome in a normoxic environment, was found to be expressed in RANKL‐stimulated osteoclast precursor cells. Induction of LSD1 by RANKL stabilized the expression of HIF‐1α protein, thereby promoting glycolysis, in conjunction with up‐regulation of the transcription factor E2F1. Analyses of cis‐eQTL revealed that higher HIF‐1α expression was associated with increased bone erosion in patients with RA. Inhibition of LSD1 decreased pathologic bone resorption in mice, both in models of accelerated osteoporosis and models of arthritis and inflammatory osteolysis. Conclusion LSD1 metabolically regulates osteoclastogenesis in an energy‐demanding inflammatory environment. These findings provide potential new therapeutic strategies targeting osteoclasts in the management of inflammatory arthritis, including in patients with RA.